Surgical repair of a chronic rupture of the rectus femoris muscle at the proximal musculotendinous junction in a soccer player - Straw, R.; Colclough, K.; Geutjens, G. (British Journal of Sports Medicine, 2003)
A rare case is presented of a longstanding rupture of the rectus femoris muscle at the proximal musculotendinous junction in a semiprofessional soccer player. Its different and unique presentation, the surgical repair, and the remarkable functional recovery are discussed.